Acquired Hemophilia A with Gastrointestinal Bleeding - Narae Park; Jin Seok Jang; Jae Hwang Cha (Korean Society of Gastrointestinal Endoscopy, 2020)
Peptic ulcer disease is the most common cause of acute gastrointestinal bleeding, followed by variceal bleeding, Mallory-Weiss syndrome, and malignancy. On the contrary, acquired hemophilia A is a very rare hemorrhagic disease, which usually manifests with musculocutaneous bleeding, caused by autoantibodies against coagulation factor VIII. A 78-year-old man presented to the Emergency Department with melena. Dieulafoy's lesions were observed on, and endoscopic cauterization was performed. However, the patient complained of back pain and symptoms indicative of upper gastrointestinal bleeding. Abdominopelvic computed tomography was performed, and hematoma in the psoas muscle was detected. Antibodies against coagulation factor VIII were confirmed with a blood test, and the diagnosis of acquired hemophilia A was made. Here, we report a case of acquired hemophilia A presenting with upper gastrointestinal bleeding symptoms and present a brief review of literature.